Informality and structural transformation - Orhan Erem Atesagaoglu; Deniz Bayram; Ceyhun Elgin (Central Bank Review (CBR), 2017)
In this paper, we investigate the evolution of the informal sector through structural transformation. We develop both a three-sector and a five-sector dynamic general equilibrium (DGE) model, which can simultaneously account for structural transformation between agriculture, industry and services, and between the informal and formal sectors. First, we incorporate the informal sector into an otherwise two-sector (agriculture and non agriculture) DGE model. Then, we augment this model and build a five-sector DGE model extending the non-agricultural sector into industry and services, to separately account for the evolution of informality in these two sectors. The calibrated model performs remarkably well in accounting for the evolution of the sectoral employment shares and the size of the informal sector. Finally, we use panel data econometric tools to investigate the empirical relationship between structural transformation and the informal sector and find a strong negative relationship between the size of non-agricultural sector and informality.
Keywords: 330; Informality; Structural transformation; DGE models; Panel data